The Impact of the Industrial Revolution 4.0 on Employment in Indonesia - ., Ilyas; Nuraini Dwiputri, Inayati; ., Isalman; ., Wahab; Suseno, Sandy (KnE Social Sciences, 2020)
This research was conducted to find out the impact of the Industrial Revolution 4.0 on employment in Indonesia. The method used in this study is a qualitative research method with data in the form of literature review and analyzed with content analysis. The results of this study indicate that the 4.0 industrial revolution has hit the world, including Indonesia. The basis of the 4.0 Indonesian Revolution lies in the progress in communication and connectivity compared to technology. The Industrial Revolution 4.0 was marked by the emergence of technological breakthroughs in a number of fields, including robotics, artificial intelligence, nano technology, quantum computing, biotechnology, the Internet of Thing (IoT), 3D printing, and autonomous vehicles. This revolution creates opportunities and of course saves the various challenges that must be faced. The industrial revolution has significantly affected labor aspects. The policies that can be taken by the government to improve labor capabilities are: First, harmonization of standardization and competency certification through cross-sectoral, cross-regional, and cross-country business partner cooperation, within the framework of market openness. Second, the development of partnership programs between the government and business / industry and between the central government and regional governments to improve the quality of the workforce. Third, improving governance in organizing training programs to accelerate worker certification. Fourth, expanding economies of scale towards sectors / sub-sectors with high productivity. The conclusions of this research: increasing the workforce and decreasing unemployment, as well as the increasing number of young people who succeed in digital business, shows that Indonesia has successfully exploited the opportunities of the Industrial Revolution 4.0. Keywords: Industrial Revolution 4.0, Technology, Labor